2020
DOI: 10.25077/jpi.22.3.292-305.2020
|View full text |Cite
|
Sign up to set email alerts
|

Evaluasi Konsumsi Protein dan Energi terhadap Produksi Susu Sapi Perah Awal Laktasi

Abstract: Penelitian bertujuan untuk mengevaluasi hubungan konsumsi protein dan energi terhadap bobot badan kering kandang dan laktasi serta produksi susu di bulan pertama awal laktasi. Materi yang digunakan adalah 24 ekor induk sapi perah peranakan FH bunting 8 bulan sampai 1 bulan setelah melahirkan. Penelitian dilakukan secara observasional dan penentuan sampel dilakukan dengan cara purposive sampling. Variabel yang diamati yaitu bobot badan, konsumsi protein kasar (PK) dan total digistibel nutrient (TDN) setiap ming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Nugraha et al (2015) stated that protein consumption has a positive relationship with the protein content in milk, that is, the more protein consumption of dairy cows, the higher the protein content in milk. Adi et al (2020) confirmed that the protein content in milk is influenced by protein consumption from the feed given, protein consumption will later become a source of amino acids during milk protein biosynthesis. Consumption of dairy cow mother protein will partially break down into peptides which will then turn into amino acids, then amino acids will be absorbed in the small intestine and then flowed through the blood and will enter the secretory cells of the udder which will then be synthesized into milk protein.…”
Section: Relationship Of Consumption Of Nutrient With Quality Of Milkmentioning
confidence: 81%
See 1 more Smart Citation
“…Nugraha et al (2015) stated that protein consumption has a positive relationship with the protein content in milk, that is, the more protein consumption of dairy cows, the higher the protein content in milk. Adi et al (2020) confirmed that the protein content in milk is influenced by protein consumption from the feed given, protein consumption will later become a source of amino acids during milk protein biosynthesis. Consumption of dairy cow mother protein will partially break down into peptides which will then turn into amino acids, then amino acids will be absorbed in the small intestine and then flowed through the blood and will enter the secretory cells of the udder which will then be synthesized into milk protein.…”
Section: Relationship Of Consumption Of Nutrient With Quality Of Milkmentioning
confidence: 81%
“…The coefficient of determination is 0,382 which means that the effect of consumption of nutrient on milk production of dairy cow is 38,2%. Adi et al (2020) states that one way to optimize milk production and quality can be done by meeting the nutritional needs of livestock, especially TDN and protein during the dry period of the cage and early lactation. Juodtienze et al (2013) states that nutrient consumption has a positive correlation with milk production, that is, more protein consumption will be followed by increased milk production.…”
Section: Relationship Of Consumption Of Nutrient With Milk Productionmentioning
confidence: 99%
“…This is related to the nutritional status of cattle which will affect the production of reproductive hormones, basal feed between cattle in this study has different types, hence livestock have different levels of nutrient consumption. Adi et al (2020) stated that BCS is a picture of a cow to evaluate the availability of body fat, the fat contained in the cow's body will be used as a precursor to the hormone estrogen which will affect the onset of oestrus signs shown by the cow. Pereira et al (2018) will stimulate reproductive hormones to be secreted, due to the fact that nutrients will be used for general metabolism first and will be used for reproduction.…”
Section: Effect Body Condition Score On Conception Ratementioning
confidence: 99%